Stock selection by using fundamental analysis and technical analysis - Liu, Jiahuan (2019)
The financial sector hires many analysts, strategists and fund managers to do one thing: beat the market. Analysts are to find undervalued stock, strategists are to predict the direction of the market and various sectors, and fund managers are to put all together to outperform their benchmark. A fundamental analyst believes that by analysing company strategy, management, product, financial statistics and other quantifiable numbers will help to choose stocks that will outperform the market. A technical analyst believes that the chart, volume, momentum, and an array of technical indicators hold the keys to superior performance. This project is based on Singapore Exchange stock market, it analysed 27 stocks in industry of food products, which include both local and foreign companies. These companies provide vary from basic daily diet to restaurant supplies. At initial stage, 27 stocks are studies with past year financial statements which including income statement, balance sheet and cash flow. Additional financial information was also retrieved from Bloomberg Terminal, which including enterprise value, price ratios and debt ratios. Through analysis of various financial figures, a list of important indicators was selected as criteria of evaluating financial and business stability of the companies behind each stock. By using correlation function between each fundamental indicators and increment (decrement) of following year of each stock, eventually 5 most related indicators were selected which are shares equity over total liabilities and equities, trailing 12-month EBITDA margin, return on common equity, cash from investing activities and net changes in cash. By using these 5 indicators, a list of stocks was selected for further study and analysis. This list contains 16 stocks which are Yeo Hiap Seng Limited, Oceanus Group Limited, Edition Ltd., Global Palm Resources Holdings Limited, Kencana Agri Limited, China Star Food Group Limited, United Food Holdings Limited, First Resources Limited, Fraser and Neave, Limited, JB Foods Limited, Bumitama Agri Ltd., China Kangda Food Company Limited, Zhongxin Fruit and Juice Limited, Indofood Agri Resources Ltd., Sino Grandness Food Industry Group Limited, Wilmar International Limited. However, due to incomplete information and stock price instability, China Kangda Food Company Limited and Zhongxin Fruit and Juice Limited were removed from the shortlist. In the section of technical analysis, five technical indicators were selected to study the relationship between their movement trend and stock price changes. These 5 indicators are Bollinger Band, Directional Movement Index, Moving Average Convergence Divergence, Moving Average, and Relative Strength Index. To study the rate of return of each indicator, separate simulation using Metastock on year 2015 and year 2017 were conducted, since in 2015 the stock was a bearish market and 2017 was a bullish market. This was to test the indicators in different market trend to result in rational rate of return to beat the market. Through both simulations, Moving Average was the most stable indicator to both survive in the bearish market and seize great of return in bullish market. To verify the reliability of selected indicator, Moving Average, additional simulation for year 2018 was conducted. And results show even in a bearish stock market in year 2018, considerable amount of return were still expectable. All the simulations for other indicators showed either small amount of returns or undesired loss for year 2018, but moving average achieved considerable 64.83% of returns. In conclusion, as for stocks in food product industry in Singapore Exchange (SGX), by using properly conducted fundamental analysis to filter stocks, and then using most appropriate technical analysis were able to expect considerable amount of returns in both bullish and bearish market.